Proficiency and Interlaboratory Variability in the Determination of Phthalate and DINCH Biomarkers in Human Urine: Results from the HBM4EU Project - Mol, Hans G.J.; Elbers, Ingrid; Pälmke, Claudia; Bury, Daniel; Göen, Thomas; López, Marta Esteban; Nübler, Stefanie; Vaccher, Vincent; Antignac, Jean Philippe; Dvořáková, Darina; Hajšlová, Jana; Sakhi, Amrit Kaur; et al. (Toxics, 2022)
A quality assurance/quality control program was implemented in the framework of the EU project HBM4EU to assess and improve the comparability of biomarker analysis and to build a network of competent laboratories. Four rounds of proficiency tests were organized for 15 phthalate and two DINCH urinary biomarkers (0.2–138 ng/mL) over a period of 18 months, with the involvement of 28 laboratories. A substantial improvement in performance was observed after the first round in particular, and by the end of the program, an average satisfactory performance rate of 90% was achieved. The interlaboratory reproducibility as derived from the participants’ results varied for the various biomarkers and rounds, with an average of 24% for the biomarkers of eight single-isomer phthalates (e.g., DnBP and DEHP) and 43% for the more challenging biomarkers of the mixed-isomer phthalates (DiNP, DiDP) and DINCH. When the reproducibility was based only on the laboratories that consistently achieved a satisfactory performance, this improved to 17% and 26%, respectively, clearly demonstrating the success of the QA/QC efforts. The program thus aided in building capacity and the establishment of a network of competent laboratories able to generate comparable and accurate HBM data for phthalate and DINCH biomarkers in 14 EU countries. In addition, global comparability was ensured by including external expert laboratories.
CRIS-Team Scopus Importer:2022-02-04
Keywords: External quality assurance scheme (EQUAS); HBM4EU; Human biomonitoring (HBM); Interlaboratory comparison investigation (ICI); Proficiency testing; QA/QC